Use Rule of One: x^1 = x
6 × x^3 + 1 × z/3
Simplify 6 × z^3/3 to 2z^3
2z^3 + 1 × z/3
Simplify 1 × z/3 to z/3
<u>= 2z^3 + z/3</u>
2 large pizzas and 2 medium pizzas
Step-by-step explanation:
=( n-2)180
= ( 4 - 2 )180
= 360
So, 144 + 90 + m<2 +m<1 = 360
144 + 90 + 85 + m<1 = 360
319 + m<1 = 360
m<1 = 360 - 319
m<1 = 41
their is an unknown angle so let's call it x
let's find x first ( m<6=49)
x + m<6 = 180
x + 49 = 180
x = 180 - 49
x = 131
Now let's find m<7
m<7 + 38 + m<4 + x = 360
m<7 + 38 + 85 + 131 = 360
m<7 + 254 = 360
m<7 = 360 - 254
m< 7 = 106
This is the Pythagorean theorem where the 2 legs of a triangle squared add up to equal the squared hypotenuse (a^2 + b^2 = c^2)
The equation would be
12^2 + 5^2 = x^2
144 + 25 = 169
The square root of 169 = 13
Answer - 13 ft
Answer:
56 times 52 times 76 divide by 4 = ? times 3 dont forget to add cm cubed at the end
Step-by-step explanation: